Alcohol content in the 'Hyper-Reality' MTV show 'Geordie Shore' - Lowe, Eden; Britton, John; Cranwell, Jo (Oxford University Press, 2018)
Aim: To quantify the occurrence of alcohol content, including alcohol branding, in the popular primetime television UK Reality TV show 'Geordie Shore' Series 11.